A sustainable perspective of microalgal biorefinery for co‐production and recovery of high‐value carotenoid and biofuel with CO2 valorization. (22nd May 2020) - Dineshkumar, Ramalingam; Sen, Ramkrishna
Abstract: Process biotechnology can play a very important role in addressing contemporary global challenges in the areas of energy, the environment, and healthcare. This review discusses the development of a biorefinery model using sustainable feedstocks such as microalgal biomass, with multiple benefits. As a case study, it demonstrates the development of a microalgal biorefinery to produce lipid for biofuel and carotenoids like lutein for healthcare applications, along with CO2 mitigation. However, there has been a question mark regarding the economic viability of microalgal biorefinery, mainly for low biomass and product yields and discrete downstream processing steps. To provide sustainable solutions for these technological challenges, process intensification strategies can be implemented to enhance the yields of biomass‐derived biofuels and value‐added products. This article investigates the design aspects of photo‐bioreactors to enhance biomass productivity and CO2 sequestration. Despite efforts made by researchers to improve product yields, there is ample scope to improve the economic viability of lutein and lipid production by integrating upstream and downstream operations to reduce the cost associated with the process. The future of algal biorefineries will rely on the development of rationally integrated genome and process‐scale engineering strategies to improve further the production of lipid and carotenoids. This review critically analyzes the current state of the art and presents the future prospects for microalgal biorefinery to address some of the challenges in the areas of healthcare, energy, and the environment. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd